2020
DOI: 10.3390/plants9081026
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Resistance in Farmer-Preferred Cassava Cultivars from Ghana to a Mixed Infection of CBSV and UCBSV

Abstract: Cassava brown streak disease (CBSD) caused by the Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) is a threat to cassava production in Africa. The potential spread of CBSD into West Africa is a cause for concern, therefore screening for resistance in farmer-preferred genotypes is crucial for effective control and management. We multiplied a selection of eleven cassava cultivars grown by farmers in Ghana to test their response to a mixed infection of CBSV (TAZ-DES-01) and UCBSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…We therefore assume a constant distribution of cassava production across Uganda over time. We also assume that all cassava is equally susceptible to infection by CBSIs, which is consistent with currently available evidence [30,31]. Similarly, evidence to date does not indicate major differences in either the yield impact or geographic distribution of the two CBSIs [32].…”
Section: Discussionsupporting
confidence: 85%
“…We therefore assume a constant distribution of cassava production across Uganda over time. We also assume that all cassava is equally susceptible to infection by CBSIs, which is consistent with currently available evidence [30,31]. Similarly, evidence to date does not indicate major differences in either the yield impact or geographic distribution of the two CBSIs [32].…”
Section: Discussionsupporting
confidence: 85%
“…This magnitude of CBSD severity can be attributed to a lack of CBSD resistance alleles in the Nigerian germplasm. A similar outcome was noted by Elegba et al (2020) , who reported less than 50% survival rate for Ghanaian cassava genotypes tested against CBSV and UCBSV under screen-house conditions. Likewise, Winter et al (2019) reported moderate to severe foliar symptoms when 238 South American cassava genotypes were assessed for resistance to CBSVs.…”
Section: Discussionsupporting
confidence: 81%
“…We selected 11 cassava cultivars or landraces popular with farmers in Ghana ( Table 1 ). These cultivars have varying degrees of susceptibility to CMD and CBSD ( Elegba et al, 2020 ). We screened the selected cultivars for production of OES, a critical initial step required for the induction of FEC and subsequent genetic transformation.…”
Section: Resultsmentioning
confidence: 99%